Drug target identification using a trypanosome overexpression library - Begolo, Daniela; Erben, Esteban D.; Clayton, Christine (Antimicrobial agents and chemotherapy, 2014)
Elucidation of molecular targets is very important for lead optimization during the drug development process. We describe a direct method to find targets of antitrypanosomal compounds against Trypanosoma brucei using a trypanosome overexpression library. As proof of concept, we treated the library with difluoromethylornithine and DDD85646 and identified their respective targets, ornithine decarboxylase and N-myristoyltransferase. The overexpression library could be a useful tool to study the modes of action of novel antitrypanosomal drug candidates.